2007
DOI: 10.1007/s11606-007-0416-9
|View full text |Cite
|
Sign up to set email alerts
|

“Could this Be Something Serious?”

Abstract: BACKGROUND: Previous work suggests that exploration and validation of patients' concerns is associated with greater patient trust, lower health care costs, improved counseling, and more guideline-concordant care. OBJECTIVE:To describe physicians' responses to patients' worries, how their responses varied according to clinical context (straightforward versus medically unexplained symptoms [MUS]) and associations between their responses and patients' ratings of interpersonal aspects of care.DESIGN: Multimethod s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(82 citation statements)
references
References 47 publications
5
77
0
Order By: Relevance
“…This result is consistent with previous studies on cancer patients, which demonstrated that physicians and nurses rarely respond to patients' emotions with empathy 6, 7, 8, 9, 10. After the course, the nurses responded to 54% of the patients' emotions with empathy, meaning that the use of empathic responses more than tripled.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with previous studies on cancer patients, which demonstrated that physicians and nurses rarely respond to patients' emotions with empathy 6, 7, 8, 9, 10. After the course, the nurses responded to 54% of the patients' emotions with empathy, meaning that the use of empathic responses more than tripled.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, oncology physician assistants, nurse practitioners and nurse clinicians responded to patients' emotions with empathic language 30% of the time 8. Similarly, physicians responded to empathic opportunities during routine primary care and surgery office visits in 15–21% of primary care cases and in 38% of surgical cases 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done by interrupting the visit momentarily to seek the patient’s perspective on a companion’s statement, perhaps by asking the patient, “Have you had a chance to talk together about this?,” “Tell me what you’ve been thinking,” or saying, “It’s only natural for people to have different perspectives about these kinds of things, especially as things change.” Open communication will hopefully result in shared attentional focus, voicing of multiple perspectives, greater patient participation in deliberations and decisions, determination of the degree to which there is agreement among the parties, and avoidance of implicit assumptions about the patient’s values and preferences. (10, 12, 30) Executing this simple action, like any new communication behavior, requires awareness and training: physicians must recognize in-the-moment when a companion is speaking on behalf of a patient; decide whether this particular instance will influence decision-making; and ultimately create a “multipartial alliance” between all parties, while still prioritizing the interests of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…When physicians offer empathy, encouragement, and active help, patients are more likely to feel that their physicians are trustworthy and supportive. Feeling responded to with empathy was found to be distinct from being given reassurance, which may paradoxically raise the patient's anxiety (Epstein et al, 2007).…”
Section: Introductionmentioning
confidence: 96%